Analisis Pengaruh Kinerja Keuangan terhadap Return Total Saham pada PT Elnusa Tahun 2009-2015 - Khusniatul Wardah (Jurnal Maksipreneur, 2017)
This study aims to analyze the influence of fundamental factors of Current Ratio, Debt to Equity Ratio, Net Profit Margin and Total Assets Turn Over toward stock of total return on PT Elnusa, Tbk in 2009-2015. The empirical purpose is to test the signalling theory empirically through the four variables toward stock of return. Data that used in this study was obtained from secondary quantitative interim consolidated quarterly reports of companies. The multiple regression technique is used to test the effects of CR, DER, NPM, and TATO toward the stock of total return.